Synergizing Professional and Entrepreneurship Education in Chinese Private Colleges: A Grounded Theory Approach - Jiangyan Sun; Md Nazirul Islam Sarker; Fengyun Yi (SAGE Open)
The fusion of professional and entrepreneurship education is increasingly recognized as vital for fostering economic growth and innovation, particularly in rapidly evolving economies such as China. This study addresses the need to integrate these educational models in Chinese private colleges to enhance students’ entrepreneurial competencies and career readiness. This study aims to develop and evaluate a cooperative model that integrates professional, entrepreneurial, and experiential learning to enhance students’ entrepreneurial intentions, competencies, and career readiness in Chinese private colleges. Using grounded theory methodology, this study conducted in-depth interviews with 65 students from 3 private colleges across different regions of China. The data were coded through open, axial, and selective coding processes to identify core factors influencing the integration of professional and entrepreneurship education. The analysis revealed three core categories influencing integration: value synergy, training system coherence, and platform resource synergy. These categories were further refined into seven main factors, leading to the development of a “Trinity” cooperative model focusing on “value-system resources” that integrates professional, entrepreneurial, and experiential learning. The “Trinity” model emphasizes the interconnectedness of educational streams and the necessity of experiential learning. This approach addresses existing challenges, such as fragmented educational frameworks and limited resources. The model is designed to enhance students’ entrepreneurial intentions, competencies, and career readiness, aligning with national innovation-driven development strategies. Integrating professional and entrepreneurship education through the “Trinity” cooperative model offers a comprehensive framework for educational reform in Chinese private colleges. This integration can significantly improve students’ entrepreneurial capabilities, contributing to social development goals.